Armenia : First Review under the Stand-By Arrangement-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Armenia. (IMF Staff Country Reports; Country Report ;, 2019)
This paper highlights Republic of Armenia's First Review Under the Stand-By-Arrangement. Armenia's economic performance is strong with healthy growth, low inflation, a stable financial system, with increasing foreign reserves and higher revenues. Despite fiscal overperformance, it is key to maintain the reform momentum to strengthen revenue mobilization, including by completing reforms to property taxation. Implementation of the authorities' reform agenda including efforts to improve governance by establishing a holistic anti-corruption framework, will bolster sustainable and inclusive growth. The monetary policy framework's focus on price stability has served Armenia well. The authorities' implementation of Basel III measures will raise the resilience of the financial system, while their plans to develop the capital market and improve access to finance are also welcome.